Phase Frequency Detector and Charge Pump for Low Jitter PLL Applications - Sung Sik Park; Ju Sang Lee; Sang Dae Yu (International Journal of Electrical and Computer Engineering (IJECE), 2018)
In this paper a new technique is presented to improve the jitter performance of conventional phase frequency detectors by completely removing the unnecessary one-shot pulse. This technique uses a variable pulse-height circuit to control the unnecessary one-shot pulse height. In addition, a novel charge-pump circuit with perfect current-matching characteristics is used to improve the output jitter performance of conventional charge pumps. This circuit is composed of a pair of symmetrical pump circuits to obtain a good current matching. As a result, the proposed charge-pump circuit has perfect current-matching characteristics, wide output range, no glitch output current, and no jump output voltage. In order to verify such operation, circuit simulation is performed using 0.18 μm CMOS process parameters.